HACCP ADMINISTRATIVE SYSTEM IN FOOD SERVICES: A REVIEW OF DIMENSIONS OVER THE TIME PERIOD 2018 TO 2022 - SOLANGE MARÍA ARTIEDA CARASSA, BLONDIE (2024)
A QUALITY FOOD SERVICE REQUIRES THE EFFORT OF ADMINISTRATIVE MANAGERS IN PURSUIT OF TRAINING AND AWARENESS. THIS DIMENSIONS REVIEW ARTICLE AIMS TO HIGHLIGHT THE EVIDENCE PRESENTED BY AUTHORS ON HACCP ADMINISTRATIVE MANAGEMENT. AS A METHODOLOGY, A REVIEW OF ARTICLES FROM THE SCIENTIFIC LITERATURE WAS CARRIED OUT IN THE DATABASES OF REDALYC, SCIELO, SCIENCEDIRECT, DOCTORAL REPOSITORIES, ORGANIZATIONAL REGULATIONS, MINISTRY REGULATIONS, HEALTH REGULATIONS, BASE BOOKS. ARTICLES WHOSE CONTEXT HAS BEEN DEVELOPED IN LATIN AMERICAN COUNTRIES WERE CONSIDERED: COLOMBIA, CUBA, MEXICO, AND PERU. AS A RESULT, 6 ARTICLES WERE OBTAINED: 3 FROM REDALYC, 2 FROM SCIELO AND 1 DOCTORAL REPOSITORY, WHICH CONTAIN THE MOST RELEVANT DIMENSIONS AND MET THE OBJECTIVE OF THIS REVIEW. LIKEWISE, 42% OF THE SELECTED ARTICLES WERE RESEARCH CARRIED OUT IN PERU, 16.5% CUBA, 25% MEXICO AND 16.5% IN COLOMBIA. FINALLY, IT IS CONCLUDED THAT THE ARTICLES DETECTED AND GROUPED IN THE STRUCTURAL-FUNCTIONALIST POSITION PROPOSE THE STANDARD DIMENSIONS OF LEARNING TO IMPROVE AND GUARANTEE QUALITY IN FOOD SERVICES. THIS REVIEW ARTICLE IS EXPECTED TO CONTRIBUTE TO FUTURE RESEARCH. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.